Public Policy Analysis in Stunting Reduction: A Review of National Programs and Strategies - Yusnita, Mila; Kurniawan, Iwan; Hakim, Azis (Jurnal Indonesia Sosial Sains, 2024)
Stunting remains a severe problem in public health, including in Indonesia, and tackling it requires cross-sectoral efforts and integrated public policies. This study analyzes public policies on stunting reduction, especially national programs and strategies in Indonesia. The research method used is public policy analysis, including identifying, describing, and evaluating existing policies and factors influencing their implementation. The study collected data from various sources, including policy documents and academic literature. The results of the analysis show that the Indonesian government has implemented various national programs and strategies to reduce stunting. These programs include nutrition interventions, maternal and child health services, health education, and community empowerment. The national strategy adopted includes a cross-sectoral approach, active community participation, increased accessibility, and health system strengthening. Nevertheless, implementing public policies to stunt reduction is faced with various challenges. These challenges include budget constraints, suboptimal cross-sectoral coordination, public awareness, and environmental factors affecting child nutrition. In addition, evaluation of the impact and effectiveness of the program is also an essential focus in improving the success of stunting reduction efforts. The study suggests several policy recommendations to improve the effectiveness of stunting reduction in Indonesia. The recommendations include increasing budget allocations for nutrition programs, improving cross-sectoral coordination through establishing more effective coordination mechanisms, increasing community participation through a community-based approach, and strengthening regular program monitoring and evaluation.